When Only the Second Best Will Do: Economic Reform and Intra‐Industry Trade in Australia's Automotive Industry1. Issue 4 (6th October 2016) - Gruen, Nicholas
Abstract : This paper explores the Industry Assistance Commission's (IAC's) 1974 and 1981 reports on Australia's automotive industry. Although it is sympathetic with the Commission's pursuit of freer trade, it illustrates how the IAC's reports exemplified important foibles of economic expertise. As bureaucratic and political enthusiasm for trade liberalisation grew from the late 1960s on, the free trade versus protection dichotomy crowded out the significance of intra‐industry trade for designing the transition to freer trade. The paper argues that in it's failure to properly consider intra‐industry trade, the IAC and the professional milieu it embodied was not the simple product of technical inadequacies of economics at the time. Rather it was driven by the uncompromising failure of the conversation it conducted. The paper concludes with a postscript on developments since the Commission's 1981 report.